Mirrors or Mirages? Changes occurred in Spain and Poland between 1976 and 1982 as reflected in respective political weekly newspapers - Dulska, Anna Katarzyna (Historia y Comunicación Social, 2021)
The present paper analyses narratives about Spain and Spanish transformation published by an influent Polish weekly newspaper “Polityka” on one hand, and about Poland and its social dynamics in a reformist Spanish weekly newspaper “Cambio 16”, on the other. The time framework is a period from 1976 to 1982, crucial for both internal affairs, as well as for bilateral relations between the two states. The research attempts to answer the question whether these newspapers searched for a mirror that would help in mutual understanding or rather for a mirage to defend domestic situation and concludes that, indeed, interpretative framing of informative contents on the other country were frequently used to structure social perceptions of own affairs.